Social and Economic Empowerment for Village Women as a Strategy of Village Development - Kushandajani Kushandajani (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
The issuance of Law No. 6/2014 that is followed with the distribution of village fund has led the rise of program initiatives from village people. One of the crucial elements of development that needs for attention is social and economic development for women. Women's roles in these two areas are significant as compared to the other sectors like politics. Developing women in these two sectors is expected to encourage further development in the village. The research aims to identify the involvement of women in village development, in one village in Central Java, Lerep Village, Ungaran Barat District, Semarang Regency, through two domains: social and economic in 2017. This research is based on qualitative research using first-hand data collected from interviews with selected informants. This research used a case study as an approach and was focused on one village, namely Lerep, Semarang District, Central Java. In Lerep, we can see that the government have strived to a prioritized woman in their empowerment programs. The areas of development include health, education, domestic violence minimization, agriculture, entrepreneurship, and poverty reduction. As a result, women in Lerep could gain more income and enjoy some public facilities provided by the village government, which contribute to the improvement of woman health. In the future, there is a need to encourage woman empowerment as a framework for village development. Therefore, the advantage of the village fund will bring further impacts on society as a whole.